Interruption of acute platelet-dependent thrombosis by the synthetic antithrombin D-phenylalanyl-L-prolyl-L-arginyl chloromethyl ketone. - Hanson, S R (1988)
Since the antithrombin action of heparin fails to interrupt arterial thrombosis, a mediating role for thrombin (EC 3.4.21.5) in the formation of high-shear platelet-dependent thrombus has been unproven. To determine whether thrombin is important in acute arterial thrombus formation and to assess the therapeutic potential of inhibiting its action, the effects of the synthetic covalent antithrombin D-phenylalanyl-L-prolyl-L-arginyl chloromethyl ketone (FPRCH2Cl) on arterial-flow vascular graft thrombosis and occlusion have been studied in a nonhuman primate model. Continuous intravenous infusion of FPRCH2Cl (100 nmol/kg per min) into vascular graft-bearing baboons (Papio anubis) abolished (i) vascular graft 111In-platelet deposition, (ii) vascular graft occlusion, (iii) thrombus-associated in vivo release of platelet-specific proteins and fibrinopeptides, (iv) platelet hemostatic plug formation, (v) thrombin-induced platelet aggregation ex vivo, and (vi) thrombin-induced blood clotting. The effects of FPRCH2Cl largely disappeared within 15 min after the infusion had been discontinued. FPRCH2Cl produced no detectable cardiovascular or other acute side effects. In contrast, sustained comparably anticoagulating levels of heparin had no effect upon 111In-platelet graft deposition, graft occlusion, platelet function as measured by the bleeding time, platelet aggregation ex vivo, or release of platelet-specific proteins in vivo. We conclude that thrombin is the principal mediator of platelet-dependent hemostatic plug formation and of the formation of platelet-dependent high-flow acute graft thrombosis and occlusion. Moreover, FPRCH2Cl or other synthetic antithrombins may provide effective antithrombotic therapy for both arterial and venous thrombosis by simultaneously inhibiting platelet activation and fibrin formation.